Comparison of Mental Health between First-Year College Students Residing in Living-Learning Communities and Traditional On-Campus Housing - Wiles, Heather, L (East Carolina University, 2013)
Mental health concerns such as stress, college adjustment, and symptoms of anxiety and depression increase during college. Living Learning Communities (LLCs) have become more prevalent on college campuses and are an unexplored avenue for addressing these concerns. LLCs are residential programs building faculty-staff-student community through themed learning in and outside the classroom. LLC research focuses on academic outcomes, with scarce attention to mental health effects or LLC comparisons. This study’s purpose is to compare the mental health and academic performance of Jarvis Leadership Program, Wellness LLC, and non-LLC students. The results of the study will address gaps in the literature regarding mental health effects of LLCs, and comparative effects of differently themed LLCs on mental health and academic performance. The project employs a quasi-experimental design with three groups: first-year students in Jarvis Leadership Program (n=74), Wellness LLC (n=34), and living on-campus but not an LLC (n=60). Recruitment strategies include residence hall flyers, attending residence hall meetings, manned stations on the halls, and LLC distribution list emails. Psychometrically sound surveys assess stress, college adjustment, and depressive and anxiety symptoms. Surveys were administered in-person and online at the beginning, middle, and end of the spring semester to examine outcome trajectories across the semester. Participants were compensated with Pirate Bucks. The study was guided by the following two research questions: 1) are there differences in mental health outcomes between students residing in LLCs and those in traditional, non-living learning residence halls? And 2) are there differences in mental health outcome between students in LLCs with different themes?.
Keywords: Living learning; Mental health; First-year students